The selection of opponents for Iran's national football team in their friendly matches: coincidence or directed diplomacy? - Javier González del Castillo (Universidad Politécnica de Madrid, 2024)
Sports diplomacy through soccer has played a key role in the Islamic Republic of Iran's penetration strategy in Latin America since 1982. This strategy has been carefully developed, backed by ideological affinities with the Latin American left. The consolidation of this relationship was significantly marked with the rise to power of Hugo Chavez in Venezuela in 1999. This led to close diplomatic and economic collaboration between Iran and Venezuela, even overcoming obstacles related to economic sanctions, and manifested itself in tangible ways through military and political support. In this sense, the soft power of soccer appears as a ratification mechanism for these agreements. The methodology applied is a mixed one, combining quantitative and qualitative analysis. In the quantitative analysis, the historical data of the Iranian national team's friendly matches have been examined in detail, identifying patterns in the choice of opponents and their possible relationship with political events. While, in the qualitative analysis, a thorough review of academic papers, government reports and political speeches has been conducted. This has allowed us to identify political discourses and narratives, as well as to understand the political motivations and objectives that influenced the choice of rivals. Ultimately, this research concludes that the choice of opponents for Iran's friendly soccer matches has not been random, but a meticulously planned diplomatic strategy. This undeniable relationship between soccer and politics reflects the importance of sport as an instrument of soft power and international projection in the Islamic Republic of Iran. Sports diplomacy, in this context, has been a crucial resource in both the internal legitimization and external projection of the Iranian regime, contributing significantly to its strategic presence in Latin America.